Músicas e imagens: recursos de mídia como ferramenta para o ensino de ciências e biologia - Oliveira, Adriane Dall' Acqua de (2010)
This dissertation presents a suggested methodology of teaching using music and images to produce video clips for teaching Science and Biology. The research was qualitative, the dialectical method and participant observation. The routing methodology of Critical Pedagogy History, present in the State of Biology Curriculum Guidelines of the State of Paraná, was used in analysis and planning activities. The objective was to propose a methodology to use technological resources of music and image in the process of teaching and learning of biology, describing mechanisms for instrumentalize teachers for using these technological resources, identifying technical and scientific terms the lyrics and pictures everyday as a learning tool. The subjects involved in this study were students in the 2nd year of high school night of a college's state schools, Ponta Grossa - Paraná. Data were collected from semi-structured questionnaires, video recordings and photographic records. As a final product, was a handbook to help teachers to produce video clips as a tool in the learning process.